2013
DOI: 10.1021/pr301107x
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Plasma Membrane Proteins Using Nanoparticle Pellicles: Comparison between Silica and Higher Density Nanoparticles

Abstract: Proteomic and other characterization of plasma membrane proteins is made difficult by their low abundance, hydrophobicity, frequent carboxylation and dynamic population. We and others have proposed that underrepresentation in LC-MS/MS analysis can be partially compensated by enriching the plasma membrane and its proteins using cationic nanoparticle pellicles. The nanoparticles increase the density of plasma membrane sheets and thus enhance separation by centrifugation from other lysed cellular components. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…Finally, the pellicles were incorporated into a mass-spectrometry-based proteomic workflow to analyze transmembrane proteins in the plasma membrane. In contrast to a prior comparison of the effect of density with nanoparticles pellicles (Choksawangkarn et al 2013), nanowire density was not found to significantly affect the enrichment of the plasma membrane. However, nanowires with a favorable aspect for pellicle formation are more easily and reliably produced with iron silicate than with silica.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Finally, the pellicles were incorporated into a mass-spectrometry-based proteomic workflow to analyze transmembrane proteins in the plasma membrane. In contrast to a prior comparison of the effect of density with nanoparticles pellicles (Choksawangkarn et al 2013), nanowire density was not found to significantly affect the enrichment of the plasma membrane. However, nanowires with a favorable aspect for pellicle formation are more easily and reliably produced with iron silicate than with silica.…”
contrasting
confidence: 99%
“…The most commonly used methods take advantage of the hydrophobicity of PM proteins (Speers and Wu 2007), or their accessibility to external chemical or physical probes (Elschenbroich et al 2010). Another method takes advantage of the higher density of plasma membrane components of the cell, and relies upon differential gradient centrifugation for separation and creation of an enriched sample (Blackler et al 2008) A fourth approach, an extension of the differential density method, has used cationic silica beads to coat the cell surface, which, after crosslinking with an anionic polymer, results in a stable nanoparticle pellicle coating the plasma membrane (Choksawangkarn et al 2013, Rahbar and Fenselau 2004, Rahbar and Fenselau 2005, Chaney and Jacobson 1983, Prior et al 2011, Li et al 2009). The resultant pellicle is large, robust and, most importantly, of a much higher density than the remaining cellular components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( a ) Human multiple myeloma cell, ( b ) cell coated with aluminacoated iron oxide nanoparticles, ( c ) PAA cross-linked coated cell, ( d ) fragment of pellicle-coated plasma membrane (modified from ref. 5)…”
Section: Figmentioning
confidence: 99%
“…The pellicle method was incorporated into proteomic strategies in 2004, using commercially available colloidal silica [3] and the original Jacobson preparation [4]. Recently a comparison has been made of pellicles comprising nanoparticles of differing densities [5]. Iron oxide particles coated with cationic alumina [6] were found to provide better enrichment than the lighter colloidal silica particles, and form the basis of the procedure presented here for enrichment of the plasma membrane from cells in suspension and, thereby, cells from tissue [7].…”
Section: Introductionmentioning
confidence: 99%